School Crisis Management Planning. Issue 4 (16th December 2020) - Elbedour, Salman; Alsubie, Futiem; Al'Uqdah, Shareefah N; Bawalsah, Joseph A
Abstract: The fundamental need for safety in schools requires research-based and trauma-informed strategies for implementing crisis management plans (CMPs). Beyond the immediate harm, longer-term potential outcomes of crises are psychological trauma and damage to the reputation for safety of the school, leading to staff attrition. An effective CMP involves (a) planning, (b) communication, (c) protocols for immediate action, and (d) protocols specific to different types of school crises. School crises can occur on the organizational level, such as natural disasters or shootings; community level, such as bullying or community violence; or individual level, such as suicide, pregnancy, or family changes. This article incorporates research from the business sector as well as education, social work, and psychology to describe the vital components of a school CMP and the role of the school mental health staff. School mental health staff must be central to development and implementation of a trauma-informed school CMP that incorporates prevention, communication, and different protocols for the various types of crises.